2016
DOI: 10.5751/ace-00834-110107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of haemosporidians in a Neotropical endemic bird area

Abstract: , an isolated coastal massif in northern Colombia that contains a large number of biomes and that is experiencing high rates of habitat loss. We sampled birds from 25 species at 2 different altitudes (1640 and 2100 m asl) and determined avian haemosporidian infection by polymerase chain reaction and sequencing a portion of the cytochrome b (cyt b) gene of the parasite. From the sampled birds, 32.1% were infected by at least 1 of 12 unique cyt b lineages of haemosporidian genera: Plasmodium, Leucocytozoon, Haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Accordingly, the geographic distribution, transmission, and prevalence of haemosporidians are often predicted by variation in water availability over time (Cornuault et al, 2013; Hernández-Lara, González-García, & Santiago-Alarcon, 2017) and space (Coon & Martin, 2013;Gonzalez-Quevedo, Davies, & Richardson, 2014;Svensson & Ricklefs, 2009;Wood et al, 2007). However, the influence of spatial heterogeneity in water availability on haemosporidians has rarely been assessed in the wild, particularly in tropical areas with substantial temporal and spatial variation in environmental conditions (Belo, Pinheiro, Reis, Ricklefs, & Braga, 2011;Galen & Witt, 2014;Gonzalez-Quevedo, Pabón, & Rivera-Gutierrez, 2016;Jones, Cheviron, & Carling, 2013;Sehgal, 2015).…”
mentioning
confidence: 99%
“…Accordingly, the geographic distribution, transmission, and prevalence of haemosporidians are often predicted by variation in water availability over time (Cornuault et al, 2013; Hernández-Lara, González-García, & Santiago-Alarcon, 2017) and space (Coon & Martin, 2013;Gonzalez-Quevedo, Davies, & Richardson, 2014;Svensson & Ricklefs, 2009;Wood et al, 2007). However, the influence of spatial heterogeneity in water availability on haemosporidians has rarely been assessed in the wild, particularly in tropical areas with substantial temporal and spatial variation in environmental conditions (Belo, Pinheiro, Reis, Ricklefs, & Braga, 2011;Galen & Witt, 2014;Gonzalez-Quevedo, Pabón, & Rivera-Gutierrez, 2016;Jones, Cheviron, & Carling, 2013;Sehgal, 2015).…”
mentioning
confidence: 99%
“…Avian malaria is a vector‐borne disease caused by intracellular protozoan parasites of the genus Plasmodium , Haemoproteus , and Leucocytozoon (Lapointe et al, 2012 ) and transmitted by insects of the order Diptera that have a worldwide distribution. This disease has been detected in tropical countries in bird species of multiple orders and families (Gonzalez‐Quevedo et al, 2016 ; Pulgarín‐R et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…This issue is becoming more important as climate change-induced territory changes are rapidly affecting the spreading of parasites and hosts [3]. In the last few decades we had observed an increase in the incidence of some infectious diseases in wild populations [4-6] and these be able to have a significant impression on wildlife populations[1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the blood parasites are generally thought to be harmless, we have evidence that infection can be harmful [26]. Studies have suggested that avian haemosporidian infection can cause reduced strength in flight; reduce speed, poor appetite, anemia, weight loss, airsacculitis, arthritis, lower reproductive success, reduced lifespan and death [6, 26-29].…”
Section: Introductionmentioning
confidence: 99%